Influência da periodontite apical na aptidão física em ratos Wistar - Bairros, Patricia Oliboni de (2021)
Chronic oral inflammatory diseases (COID) are associated with systemic outcomes, in part due to modifications in the serum levels of inflammatory mediators. Considering that COID may lead to both local and systemic low-grade pro-inflammatory state, findings from observational studies have suggested an association between different parameters of oral health and physical fitness. The aim of this study was to evaluate the influence of apical periodontitis (AP) on physical training and fitness in Wistar rats, analyzing the impact of the inflammatory load of endodontic disease in the animals' physical conditioning. This study was structured according to the ARRIVE guidelines (Animal Research: Reporting of In Vivo Experiments). Forty-eight male Wistar rats, three months old and weighing between 400-450 g were used. The animals were divided into 6 groups (n = 8): sedentary rats, with AP induction in one tooth (1AP-SED); sedentary rats, with the induction of AP in four teeth (4AP-SED); sedentary rats, without AP induction (SED); exercised rats with physical training, with AP induction in one tooth (1PA-EX); exercised rats with physical training, with the induction of AP in four teeth (4AP-EX) and exercised rats with physical training, without induction of AP (EX). AP was induced through pulp exposure, keeping the pulp chamber open for 6 weeks. The physical training of the animals was carried out through a swimming protocol for 6 weeks. After the end of the experimental period, the animals were euthanized. For the assessment of physical fitness, the following tests were performed: maximum test of physical capacity and measurement of blood lactate concentration (before and after the training protocol); evolution of body weight and body mass index; adiposity, cardiac and muscular hypertrophy (soleus and gastrocnemius). The data obtained in the maximum tests were analyzed using the two-way ANOVA test with Tukey and Sidak post hoc. The EX-group showed the highest performance in the physical test, statistically different from the SED, 4PA-SED, 1PA-EX and 4PA EX groups (p £ 0.05). Regarding the maximum test of physical capacity, no differences were found among the 1PA-EX, 4PA-EX and SED groups (p > 0.05). No differences were found between groups in the assessment of blood lactate using the repeated measures ANOVA test. The evolution of the animals' body weight, over time, was evaluated using the ANOVA test of repeated measures and post hoc Tukey. The weight of all animals was increased during the initial 5 weeks of the experiment. From that period on, with the beginning of physical training, the animals of the sedentary groups followed the linear constant of weight gain, while in the trained animals the physical exercise attenuated the weight increase. However, there were no statistical differences (p > 0.05) in relation to body weight, regardless of the presence and amount of AP, between the trained animals. Regarding the Lee index and adiposity, the 1-way ANOVA test did not find differences between groups (p > 0.05). Regarding muscle parameters, an increase in cardiac muscle mass was observed in the EX-group compared to the SED and 1PA-SED groups (p £ 0.05). Present findings revealed that AP had a negative impact on the physical fitness of Wistar rats, suggesting a doseresponse effect in the relationship between the burden of endodontic disease and the physical capacity.